Analysis of Parasites Afflicting Sangkuriang Catfish (Clarias gariepinus) at UPR SD Mina Jaya - Surya Khairunnisa; Kurnia Wati; Puspita Dewi Rani; Ellya Anggraeni; Ma’arif Arya Panca; Dio Ardy Azhari Marpaung; Bambang Wahyudi; Aldi Helfahmi; Muhammad Fadli; Rumondang; Asprin Tamba (Grouper, 2024)
Catfish (Clarias gariepinus) is a type of freshwater fish that is cultivated commercially by Indonesian people. One of the key factors for success in aquaculture is water quality. Poor water quality can cause stress to fish and lead to the proliferation of parasites. Parasites are organisms whose existence depends on other organisms. This research aims to analyze the parasites that attack sangkuriang catfish (C. gariepinus) in the SD Mina Jaya People's Hatchery Unit. It is hoped that this research activity can determine the parasites that attack catfish. Data collection was carried out using a descriptive method, with the sampling method for sangkuriang catfish (C. gariepinus) carried out randomly (random sampling). The research resulted in the identification of parasites that infect catfish in cultivation ponds at UPR SD Mina Jaya consisting of 4 types of parasites from the Phylum Nematoda. The types of parasites obtained were Dactylogyrus sp., Gyrodactylus sp., Octolasmis sp., Capilaria hepatica. The water quality in the cultivation ponds was also still classified as normal, namely a temperature of 290C, pH 8.5, and DO 7.5 mg/L.